2019
DOI: 10.1111/jnc.14662
|View full text |Cite
|
Sign up to set email alerts
|

Injury to hypothalamic Sim1 neurons is a common feature of obesity by exposure to high‐fat diet in male and female mice

Abstract: The hypothalamus is essential for regulation of energy homeostasis and metabolism. Feeding hypercaloric, high‐fat (HF) diet induces hypothalamic arcuate nucleus injury and alters metabolism more severely in male than in female mice. The site(s) and extent of hypothalamic injury in male and female mice are not completely understood. In the paraventricular nucleus (PVN) of the hypothalamus, single‐minded family basic helix‐loop helix transcription factor 1 (Sim1) neurons are essential to control energy homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 114 publications
(356 reference statements)
1
32
1
Order By: Relevance
“…We have found that exposure of mice to lard-based HF diet induces loss of liver PE, which takes place even before the onset of obesity 13 . Here, we find that loss of PE takes place also in the liver of obese mice exposed to a palm oilbased HF diet and is concomitant to hepatosteatosis.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We have found that exposure of mice to lard-based HF diet induces loss of liver PE, which takes place even before the onset of obesity 13 . Here, we find that loss of PE takes place also in the liver of obese mice exposed to a palm oilbased HF diet and is concomitant to hepatosteatosis.…”
Section: Discussionmentioning
confidence: 88%
“…In mice exposed to a palm oil-based HF diet, onset of hepatosteatosis is paralleled by loss of Grp78/Bip in pericentral hepatocytes A HF diet with 45% Kcal fat from lard has been used to study effects of lipid stress in rodents [14][15][16] . We have here modified this diet by substituting lard with palm oil 13 , which reflect more closely the lipid composition of human diets [17][18][19] . Mice were treated with LF and palm oil-based HF diet for a total of 14 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations